Assessing patient satisfaction among COVID-19 survivors in Northeast India: a cross-sectional study - Saeed, Shazina; Niazi, Farah; Kaur, Karuna Nidhi; Rana, Shweta; Singhal, Manmohan; Singh, Harpreet (Frontiers in Medicine, 2024)
This study investigates patient satisfaction among COVID-19 survivors in Northeast India, motivated by the unique long-term healthcare needs of survivors and the critical role of patient satisfaction in assessing and enhancing healthcare quality. By focusing on this underexplored region, the research aims to uncover insights that can guide improvements in patient-centered care and healthcare service delivery in similar contexts. Materials and Methods: The study was conducted using a Simple Random Sampling technique. Data were collected through telephone interviews using a semi-structured questionnaire, including the Patient Satisfaction Questionnaire-18 (PSQ-18) for analysis. The PSQ-18 yielded seven subscale scores representing different dimensions of patient satisfaction. Statistical analysis using SPSS software was conducted to summarize sociodemographic characteristics, medical history, and patient satisfaction levels, employing both descriptive and inferential statistics. Result: The results indicated a high acceptance of COVID-19 vaccination, with the majority of participants having received both doses. Patient satisfaction with healthcare services is generally positive, particularly in aspects related to doctor-patient communication and medical care quality. However, there are notable concerns regarding the affordability and timeliness of care. Regional variations across states, as well as factors like education and income, significantly influence patient satisfaction levels. Conclusions: The study revealed generally good patient satisfaction levels in Northeast India. However, challenges in